Analysis of Factors Related to Elderly Participation in Elderly Posyandu in the Working Area of the Banda Aceh City Health Centre - Thaila Nensis; Nasrul Zaman; Said Usman; Irwan Saputra; T.Maulana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: The elderly aged 60-69 years in Banda Aceh are 15,820. The coverage of the lowest number of elderly visits to elderly posyandu in the city of Banda Aceh is the Jaya Baru Health Centre (5.5%), the Lampaseh Health Centre (6.5%), and the Kuta Alam Health Centre (7.7%). Objective: This study aims to analyse factors related to the participation of the elderly in the Banda Aceh City Health Centre. Research Method: The type of research uses a cross-sectional design. The population in this study includes all older people in 3 (three) Banda Aceh City Puksesmas, namely Jaya Baru, Lampaseh, and Kuta Alam. The sample in this study amounted to 98 older people. Results: there was no relationship between accessibility and elderly posyandu participation (t= 1,356; p=0.176), there is a relationship between the availability of facilities and infrastructure and the participation of the elderly posyandu ( (t= 3.496; p=0.001), ), there was a relationship between motivation and support for elderly families (t=2.294; p=0.022), there was a relationship between the knowledge of the Posyandu program (t= 5.197; p=0.000), there was no relationship between the role of health workers and the participation of elderly posyandu at the Banda Aceh City Health Center (t=0.257; p=0.797), The factor that most affects the participation of elderly posyandu in Banda Aceh City is the knowledge of the posyandu program (t= 5.197; p=0.000). Conclusion: knowledge of the elderly posyandu program, the availability of infrastructure, motivation and support of elderly families affect the participation of posyandu in Banda Aceh City